2012
DOI: 10.1182/blood-2011-12-398792
|View full text |Cite
|
Sign up to set email alerts
|

The complement receptor 2/factor H fusion protein TT30 protects paroxysmal nocturnal hemoglobinuria erythrocytes from complement-mediated hemolysis and C3 fragment opsonization

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by complementmediated intravascular hemolysis because of the lack from erythrocyte surface of the complement regulators CD55 and CD59, with subsequent uncontrolled continuous spontaneous activation of the complement alternative pathway (CAP), and at times of the complement classic pathway. Here we investigate in an in vitro model the effect on PNH erythrocytes of a novel therapeutic strategy for membranetargeted delivery of a CAP inhibitor. TT30 is a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 52 publications
8
109
1
3
Order By: Relevance
“…FH plays a role in the protection of PNH erythrocytes, which are characterized by strongly reduced numbers of the membrane-anchored complement regulatory proteins CD55 and CD59 due to a defect in the glycosylphosphatidylinositol anchor (67). A recent report showed that targeting CCPs 1-5 of FH to sites of complement activation at the surface of PNH erythrocytes by using a chimeric molecule confers protection of these erythrocytes from C3 fragment deposition and lysis (68).…”
Section: Discussionmentioning
confidence: 99%
“…FH plays a role in the protection of PNH erythrocytes, which are characterized by strongly reduced numbers of the membrane-anchored complement regulatory proteins CD55 and CD59 due to a defect in the glycosylphosphatidylinositol anchor (67). A recent report showed that targeting CCPs 1-5 of FH to sites of complement activation at the surface of PNH erythrocytes by using a chimeric molecule confers protection of these erythrocytes from C3 fragment deposition and lysis (68).…”
Section: Discussionmentioning
confidence: 99%
“…The RBC were then incubated with sera containing eculizumab as previously described. 13,14 Briefly, a 2% suspension of RBC from PNH patients was incubated at 37°C with a pool of ABO-compatible sera from patients on eculizumab, and the complement alternative pathway was activated by mild acidification (HCl 0.016 M). At serial time points (15,30, 60, and 120 min) after complement activation the fraction of GPI-negative RBC with newly bound C3 fragments was measured by flow cytometry (AccuriC6, Becton Dickinson, NJ, USA) after staining with anti-CD59 Alexa647 (Mem43, Serotec, UK) and anti-C3d-neoantigen (A250, Quidel, CA, USA); secondary staining was performed with phycoerythrin-labeled polyclonal rabbit-anti-mouse antibodies (Dako Cytomation, Denmark).…”
Section: Kinetics Of C3 Binding In Vitromentioning
confidence: 99%
“…29,30 In addition, CR1 plays a role in the clearance of immune complexes and in phagocytosis. [31][32][33] Thus, the lower levels of CR1 expression on the red cell surface associated with the H/L and L/L genotypes 22 are expected to result in increased complement activation and C3 binding on PNH red cells.In order to test this hypothesis we investigated the kinetics of C3 binding to GPI-negative red cells in vitro 13,14 from patients with the three CR1 HindIII genotypes. When GPI-negative red cells were exposed to activated complement in the presence of eculizumab, we promptly detected C3-positive PNH red cells, the percentage of which increased with time.…”
mentioning
confidence: 99%
“…53 Risitano and co-workers reported TT30 to efficiently inhibit C3 deposition on and hemolysis of PNH RBCs. 55 Therefore, TT30 might be a suitable therapeutic, not only to inhibit intravascular hemolysis, but also extravascular hemolysis in PNH patients (Figure 2). In analogy to H17/3E7, TT30 is not effective in the inhibition of classical pathway activation.…”
mentioning
confidence: 99%